COMPARISON OF ENDOSCOPIC RETROGRADE CHOLANGIOPANCREA-TOGRAPHY, ULTRASONOGRAPHY AND FECAL ELASTASE1 IN PATIENTS WITH CHRONIC PANCREATITIS - Parunian, L.М. (World of Medicine and Biology, 2015)
Chronic pancreatitis (CP) is characterized by abdominal pain, recurring attacks of acute pancreatitis, and, as a result, exocrine and endocrine insufficiency. It is extremely complicated to clinically find exocrine pancreatic insufficiency in early stages when there are no apparent diarrhea and steatorrhea. Use of endoscopic retrograde cholangio-pancreatography (ERCP) is limited according to technical complexities and risk of complications. Clinical application of the secretin-secretin-pancreozymin (secretin-cerulein) test is significantly limited because of its invasiveness, necessity of X-ray control over location of the probe cannula, lack of international standardization and low reproducibility of results even within one clinic, the patient's great discomfort, and high complexity of the procedure for staff, not to mention high cost price of the study. Breath tests using a mixture of triglycerides labeled with carbon C13 are an effective method of pancreatic excretory function detection. But costs of reagents and the need for an expensive analyzer significantly limit application of these tests. Also, the changes in exocrine pancreatic function were detected using faecal elastase 1.The aim of this study was comparison of effectiveness of ERCP, ultrasound, and faeces elastase 1 in chronic pancreatitis diagnostics and assessment of their correlation with intensity of clinical signs of a disease.ERCP, ultrasound and faecal elastase 1 level check were administered to 29 patients with CP (22 males and 7 women) in the age 39-61. An alcohol abuse was the key etiologic reason for patients, in 9 patient it was biliary pathology, uncertain cause was in 4 patients. 10 patients have had attacks of acute pancreatitis of different severity, because of those they had received in-patient surgical treatment. 15 almost healthy people (10 men and 5 women aged 28-55 years) constituted the control group. Ultrasound check and determination of faeces elastase 1 were administered to all the group members. Biochemical markers, body mass index, duration of disease, intensity of clinical signs were also studied. Intensity of morphological changes at ERCP in patients suffering from CP for more than 5 years was certainly greater. Reduction of the faecal elastase 1 level also depended on the duration of disease. Body mass index turned out to be lower in patients with severe morphofunctional changes and CP duration more than 10 years. Biochemical markers did not significantly differ in groups with different duration of CP. Increased levels of ALT, GGT, and ALP were observed in patients with CP against the background of biliary pathology. Level of serum glucose was higher in patients with a CP anamnesis more than 10 years, but the statistically significant difference is not revealed.ERCP remains the gold standard in diagnostics of morphological changes in the pancreas in patients with chronic pancreatitis. Ultrasound examination using high-resolution devices allow to diagnose morphological changes with high accuracy, but subjectivity of this method, as well as anatomical and topographic peculiarities of a pancreas are significantly decreasing sensitivity of ultrasound diagnostics (62%). Sensitivity and specificity of faecal elastase 1 were 75% and 98% respectively. The changes of biochemical markers in groups turned out statistically insignificant. A negative correlation between the duration of disease, intensity of clinical signs, and level of elastase 1 in faeces is revealed. Thus faecal elastase 1 is a non-invasive, sensitive and specific diagnostic technique of excretory pancreatic insufficiency in patients with CP. Simplicity and availability are advantages of ultrasound diagnostics and it should be used as a screening diagnostic technique.
Keywords: chronic pancreatitis; endoscopic retrograde cholangiopancreatography; ultrasonography; fecal elastase1